Tactile Sensorimotor Intervention in Autistic Children to Reduce Tantrum Behavior - Andini, Permata Dewi; Jati, Sri Nugroho; Seftiani, Adela; Suriyanti, Suriyanti (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The WHO predicts that 1 in 600 children worldwide suffer from autism spectrum disorder. Sensory issues experienced by children with autism may be accompanied by an increase in temper tantrum behaviors, which can be managed through tactile sensorimotor intervention. This study aims to reduce tantrum behaviors related to sensory issues in children with autism through tactile sensorimotor intervention. This experimental research uses a single case experimental design with a single subject design. The subject criteria include being 3-4 years old, diagnosed with autism spectrum disorder (based on a psychological diagnosis), and having tactile sensory issues. Data collection methods include observation, interviews, and documentation. The results show that tactile sensorimotor intervention is effective in reducing tantrum behaviors in children with autism, with a reduction from 77 occurrences (40-minute duration) in the pre-test phase to 15 occurrences (10-minute duration) in the post-test. These findings have important implications for the development of sensory-based interventions for children with ASD. WHO memprediksikan bahwa 1 dari 600 anak di dunia menderita gangguan spektrum autisme. Permasalahan sensoris yang dialami anak autis dapat disertai dengan meningkatnya perilaku temper tantrum, yang dapat ditangani menggunakan intervensi sensorimotor taktil. Penelitian ini bertujuan menurunkan perilaku tantrum terkait masalah sensorik pada anak autis melalui intervensi sensorimotor taktil. Penelitian eksperimen ini menggunakan single case experimental design dengan single subject design. Subjek memiliki kriteria yaitu berusia 3-4 tahun, mengalami Autism Spectrum Disorder (berdasarkan diagnosa psikolog) dan problem sensoris taktil. Metode pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan intervensi sensorimotor taktil efektif menurunkan perilaku tantrum pada anak autis, dengan penurunan dari tahap pre-test sebanyak 77 kali (durasi 40 menit) menjadi 15 kali (durasi 10 menit) pada post-test. Temuan ini memiliki implikasi penting bagi pengembangan intervensi berbasis sensorik untuk anak dengan ASD.